2022
DOI: 10.3389/fcell.2022.943519
|View full text |Cite|
|
Sign up to set email alerts
|

Breaking the aging epigenetic barrier

Abstract: Aging is an inexorable event occurring universally for all organisms characterized by the progressive loss of cell function. However, less is known about the key events occurring inside the nucleus in the process of aging. The advent of chromosome capture techniques and extensive modern sequencing technologies have illuminated a rather dynamic structure of chromatin inside the nucleus. As cells advance along their life cycle, chromatin condensation states alter which leads to a different epigenetic landscape, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 162 publications
0
5
0
Order By: Relevance
“…The average human life expectancy has increased in recent times, and the burden of age-related diseases has increased along with it. A developing field of research is focused on the reversal of the aging phenotype via in vivo partial reprogramming through introducing Yamanaka factors ( Ocampo et al, 2016 ; Sikder et al, 2022 ). It is intriguing to see VSELs and Yamanaka factors at the crossroads of aging research, similar to making iPS cells.…”
Section: Discussionmentioning
confidence: 99%
“…The average human life expectancy has increased in recent times, and the burden of age-related diseases has increased along with it. A developing field of research is focused on the reversal of the aging phenotype via in vivo partial reprogramming through introducing Yamanaka factors ( Ocampo et al, 2016 ; Sikder et al, 2022 ). It is intriguing to see VSELs and Yamanaka factors at the crossroads of aging research, similar to making iPS cells.…”
Section: Discussionmentioning
confidence: 99%
“…A number of excellent articles concerned with chromatin changes during senescence have been published (Olan et al, 2020; Parry et al, 2018; Parry and Narita, 2016; Rocha et al, 2022; Sikder et al, 2022; Sławińska and Krupa, 2021; Swanson et al, 2015). These articles document both the similarities and differences observed comparing cellular senescence in different types of cells.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6] Aging is characterized by progressive changes and loss of cell function, and is an inexorable event faced by all organic organisms. [7] Most cancers were diagnosed over the age of 60. By the year of 2050, The World Health Organization estimated that over 20% of the global population will be over the age of 60.…”
Section: Introductionmentioning
confidence: 99%
“…During natural aging process, different aspects of cancer have been widely investigated, including individual accumulation of deleterious mutations, cancer-related immune surveillance, immunopathogenesis, immune therapy responses, genomic and epigenomic changes, and associated microbiota. [7,[9][10][11] A series of studies reported the aging microenvironment may have significant influence on tumor progression. [8,12,13] Significant studies that represent and reflect the key points and findings between the aging process and cancer genesis remain to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%